Inhaled prazosin in asthma. Issue 5 (May 1981) - Barnes, P J; Ind, P W; Dollery, C T
Abstract : Prazosin, a potent and selective alpha-adrenergic antagonist, was given by inhalation to nine asthmatic subjects aged 25-48 years (six with positive skin tests). Prazosin 0.5 mg, salbutamol 1 mg, or placebo were given by nebuliser in randomised double-blind fashion on separate days. Although all subjects showed a significant increase in FEV1, vital capacity, and maximum expiratory flow at 70% of total lung capacity after salbutamol, there was no significant difference between prazosin and placebo. This suggests that alpha-adrenergic receptors are not important in the control of bronchial tone in asthma. The weak bronchodilatation ascribed to alpha-antagonists in previous studies could be explained by other pharmacological actions of the drugs used.